Hubungan Poligami Tanpa Izin Istri Dalam Kehidupan Rumah Tangga Perspektif Hukum Islam (Studi Kasus di Desa Bengkaung Kecamatan Batulayar) - Muhammad Amri Amin; Irwan; Ami Pratama; Sadam Husen (LPPM Universitas HKBP Nommensen, 2024)
Marriage is a law that allows having one wife to four wives, polygamous marriages are permitted either in a serial manner or with the permission of the first wife provided they are able to be fair physically and mentally. In Bengkaung Village, Batulayar District, polygamy is generally carried out through unregistered marriages which cause many problems. The aim of the research is to find out polygamy according to law; to determine the relationship between polygamy without the wife's permission and household life in Bengkaung Village, Batulayar District; and to know about polygamy according to Islam. The method used is qualitative, respondents were selected by random sampling from perpetrators of unregistered marriages, from this research it can be concluded that: 1. Polygamy is permitted by law provided that there is written permission from the first wife, the husband is ready to fulfill the needs of his wives, it can be valid fair both physically and mentally; 2. Siri marriages are carried out in Bengkaung Village, Batulayar District because to cover the perpetrator's social status, to avoid the first wife not being allowed to remarry, generally the first wife does not allow her husband to remarry; 3. According to Islamic rules, serial or open polygamy is permitted for up to 4 wives provided that: the husband is capable, is able to provide for his wives both physically and mentally and is able to act fairly.